2019
DOI: 10.1007/s11469-019-00109-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Personality Characteristics and Sexual Orientation in the Risk for Sexual Addiction Among Israeli Men: Validation of a Hebrew Sex Addiction Scale

Abstract: Men having sex with men are known to exhibit heightened sexual activity. This raises the conjecture that different sexual orientations exhibit different levels of sex addiction risk, which is also affected by personality. The present study examined the prevalence of the sex addiction risk within the context of sexual orientation and personality in Israeli men while also validating the Hebrew Bergen-Yale Sex Addiction Scale (HBYSAS). Results based on 177 participants showed that the HBYSAS is appropriate for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
3
6
0
Order By: Relevance
“…Specifically, we found that a single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study of Paz et al, (Hebrew), and Anderson et al, (original English version)) [9,17]. However, in comparision with other countries, Iranians might have the same experience of sexual addiction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Specifically, we found that a single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study of Paz et al, (Hebrew), and Anderson et al, (original English version)) [9,17]. However, in comparision with other countries, Iranians might have the same experience of sexual addiction.…”
Section: Discussionsupporting
confidence: 80%
“…According to the psychometric properties of this study, the BYSAS was highly test-retest reliable (a 2week period) for screening of sexual addiction and Cronbach's alpha was for internal consistency coefficient of 0.88 and for the intra-class correlation coefficient of 0.89 that was higher than the values obtained in previous reliable studies [9,17]. In addition, the positive and significant correlations found in the Christon et al study indicated the high reliability of the BYSAS.…”
Section: Discussionmentioning
confidence: 43%
“…Specifically, we found single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study According to the psychometric properties of this study, it shows that BYSAS was highly test-retest reliable (2-week) for screening of sexual addiction and Cronbach's alpha was for internal consistency coefficient of 0.88 and for the intra-class correlation coefficient of 0.89 that was higher than the values obtained in previous reliable studies (9,16). In addition, the positive and significant correlations found in the Christon et al, study that indicated the high reliability of BYSAS.…”
Section: Discussionsupporting
confidence: 90%
“…Speci cally, we found single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study of Paz et al, (Hebrew), and Anderson et al, (original English version)) (9,16). However, all these might point to the fact that Iranians' experiences of sexual addiction similarly when compared to other countries.…”
Section: Discussionsupporting
confidence: 81%